The Prognostic Role of Circulating Tumor Cells (CTCs) in Lung Cancer - Kapeleris, Joanna; Kulasinghe, Arutha; Warkiani, Majid E.; Vela, Ian; Kenny, Liz; O'Byrne, Kenneth; Punyadeera, Chamindie (Frontiers in Oncology, 2018)
Lung cancer affects over 1.8 million people worldwide and is the leading cause of cancer related mortality globally. Currently, diagnosis of lung cancer involves a combination of imaging and invasive biopsies to confirm histopathology. Non-invasive diagnostic techniques under investigation include "liquid biopsies" through a simple blood draw to develop predictive and prognostic biomarkers. A better understanding of circulating tumour cell (CTC) dissemination mechanisms offers promising potential for the development of techniques to assist in the diagnosis of lung cancer. Enumeration and characterization of CTCs has the potential to act as a prognostic biomarker and to identify novel drug targets for a precision medicine approach to lung cancer care. This review will focus on the current status of CTCs and their potential diagnostic and prognostic utility in this setting.